Biogênese mitocondrial e marcadores de estresse oxidativo em ratos treinados e suplementados com L-Arginina - Silva, Carmem Peres Valgas da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The mitochondrion is an organelle which plays an important role in energy metabolism. It is known that both nitric oxide and exercise alone promote mitochondrial biogenesis, increasing its key transcription cofactors, among these, the peroxisome proliferator-activated receptor- coactivator (PGC)-1 (PGC-1α) and mitochondrial transcription factor A (mtTFA). However no study has evaluated the association L-arginine and exercise on mitochondrial biomarkers. The objectives of this study were to assess exercise tolerance, the redox state and mitochondrial biomarkers in trained rats supplemented with L-arginine. Methods: Wistar rats were divided into four groups: sedentary without and with L-arginine (SD; SDLA) and trained groups: with and without supplementation (TR; TRLA). Aerobic exercise was conducted in sessions of 60 min. 5 days a week for 8 weeks. L-arginine was administered orally by gavage (62.5 mg / ml / day / rat). Test of exercise tolerance with incremental speed until exhaustion was performed in the 8th week of physical training. The gastrocnemius muscle was isolated and protein expressions of mtTFA, ATP synthase subunit c, cytocrome c oxidase (COXIV), AMP-activated protein kinase (AMPK), the superoxide dismutase subtypes: Cu/Zn-SOD and Mn-SOD and neuronal nitric oxide synthase and endothelial (eNOS and nNOS) were measured in the cytoplasm and extract enriched in mitochondria by Western Blott. Fasting glucose, lipid profile, nitrite and nitrate (NOx) and MDA were also analyzed. Results: Physical training with or without L-arginine caused a reduction in blood glucose levels (approximately 8%) and plasma triglycerides (approximately 39%). While supplemented with L-arg. led to a reduction in total cholesterol (15%) compared to the SD and TR group. A significant increase in exercise tolerance in the last test in the trained animals (TR: 175% e TRLA: 229%) compared with sedentary groups. While the TRLA group presented enhanced exercise...

A mitocôndria é uma organela que desempenha importante função no metabolismo energético. Sabe-se que tanto o óxido nítrico quanto o exercício físico isolados promovem biogênese mitocondrial, aumentando seus principais indutores de biogênese, dentre esses, o coativador 1α do receptor gama ativado pelo peroxisoma proliferador (PGC-1α) e o fator de transcrição mitocondrial A (mtTFA). No entanto, nenhum trabalho avaliou a associação entre L-arginina e exercício físico sobre os biomarcadores mitocondriais. Assim, os objetivos desse trabalho foram avaliar a tolerância ao esforço, o estado redox e os biomarcadores mitocondriais em ratos treinados e suplementados com L-arginina. Métodos: Ratos Wistar foram divididos em quatro grupos: sedentários sem e com L-arginina (SD; SDLA) e grupos treinados: sem e com suplementação (TR; TRLA). Treinamento físico aeróbio foi realizado em sessões de 60 min, 5 dias na semana, por 8 semanas. A L-arginina foi administrada por via oral através de gavage (62,5 mg/ml/dia/rato). Teste de esforço físico com velocidade incremental até a exaustão foi realizado na oitava semana de treinamento físico. O músculo gastrocnêmio foi isolado e as expressões proteicas do fator de transcrição mitocondrial A (mtTFA); ATP sintase subunidade c; citocromo c oxidase (COXIV); proteína quinase ativada pelo AMP (AMPK); as enzimas antioxidantes superóxido dismutase subtipos: Cu/Zn-SOD e Mn-SOD e a óxido nítrico sintase neuronal e endotelial (nNOS e eNOS) foram medidas no citoplasma e no extrato enriquecido de mitocôndrias por Western Blott. Também foram realizadas análises plasmáticas de glicemia, perfil lipídico, além de nitrito e nitrato (NOx) e MDA plasmáticos e citoplasmáticos. Resultados: O treinamento físico aeróbio associado ou não à L-arginina promoveu redução na glicemia (aproximadamente 8%) e triglicérides (aproximadamente 39%) plasmáticos. Enquanto que a suplementação com...
Keywords: Nutrition; Nutrição; Vida - Origem; Antioxidantes; Enzimas; Mitocondria; Stress oxidativo; Arginina